A contribution to the biology of warthog (Phacochoerus africanus, Gmelin) in the Sengwa region of Rhodesia - Cumming, D H M (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1971)
To the AmaZulu a warthog is "inhlovudawana" or "little elephant"; to arrogant hunters it is the "poor man's rhinoceros"; to some writers of encyclopaediae it is a "grotesque and hideous beast"; to stockmen it has long been a carrier of diseases. Injury was added to insult with the discovery that the blood of these self-assured, often comical and certainly engaging animals supports the greater proportion of tsetse flies in the African savannas. Their significance as the primary hosts of Glossina morsitans Westw., the vectors of tryanosomiasis, justified an extended field study of warthog biology. This thesis reports four years of field work on warthogs, together with complementary observations of hand-reared warthogs (and their offspring) which roamed freely in the vicinity of the remote field station on which I live. The Sengwa Research Project, of which this study forms a part, was initiated in 1965 to study relationships between game animals and tsetse flies. One of the main problems investigated in the Sengwa Project is that of "host encounter" (Glasgow, 1961, Bursell, 1970) and how the distribution, abundance and behaviour of game animals may affect their availability to hungry tsetse flies. I have, accordingly, been concerned with discovering how warthog are dispersed in the Sengwa area and have attempted to gain some understanding of the factors, both environmental and social, which may affect or govern their dispersion and possibly population number. Intro. p. 1.
Keywords: Warthog; Warthog -- Physiology; Warthog -- Ecology